2015
DOI: 10.1177/0146645315575485
|View full text |Cite
|
Sign up to set email alerts
|

ICRP Publication 129: Radiological Protection in Cone Beam Computed Tomography (CBCT)

Abstract: The objective of this publication is to provide guidance on radiological protection in the new technology of cone beam computed tomography (CBCT). Publications 87 and 102 dealt with patient dose management in computed tomography (CT) and multi-detector CT. The new applications of CBCT and the associated radiological protection issues are substantially different from those of conventional CT. The perception that CBCT involves lower doses was only true in initial applications. CBCT is now used widely by speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 174 publications
1
27
0
Order By: Relevance
“…Tube current and voltage are operator-dependent factors and should be kept as low as possible to reduce the radiation dose, while maintaining the diagnostic quality of the image. 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tube current and voltage are operator-dependent factors and should be kept as low as possible to reduce the radiation dose, while maintaining the diagnostic quality of the image. 6 …”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that these centers should evaluate their protocols and establish different protocols for adults, adolescents, and children. The doses were measured in CTDIw, which combines the measurements of the center and the periphery of a phantom to generate a weighted dose index, 6 11 so the dose measurements were not a direct evaluation of the effective dose received by each patient. As the CTDIw describes an average dose, it can be inferred that children receive a higher dose than is recorded by the equipment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of this, CBCT is now widely used by practitioners who have not received the traditional radiation safety training of specialists in radiology. Therefore, more emphasis on radiation protection equipment, guidelines, and standardization for CBCT procedures seems reasonable [ 13 ].…”
Section: Introductionmentioning
confidence: 99%